Atmospheric chemistry of CF3CCH: Kinetics, products, mechanism of gas-phase reaction with OH radicals, and atmospheric implications-an effort for novel 'class' of refrigerant. (1st February 2023) - Zhang, Tongyun; Zhang, Chengping; Ma, Xiaoxun; Quan, Hengdao
Abstract: We use the relative method to first evaluate the atmospheric chemistry of CF3 CCH that would play significant role in novel refrigerant development. We show that rate constant ( k OH ) for the gas-phase reaction of CF3 CCH with OH radicals at 298 K is measured to be (2.15 ± 0.02) × 10 −13  cm 3 molecule −1 s −1, with Arrhenius expression as k OH =(3.40 ± 0.46) × 10 −12 exp ((-832.70 ± 38.86)/T). Subject to the short atmospheric lifetime of CF3 CCH of 53.9 d and radiative efficiency of 0.071 W m −2  ppb −1, the global warming potentials (GWPs) for 20, 100, and 500 yr are 42, 11, and 3, respectively. CF3 CCH emissions are predicated to produce CO, CO2, COF2 and CF3 O3 CF3 as the main carbon-containing products. The photochemical ozone creation potential of the CF3 CCH is 2.49 and 1.05 in Northwestern European and US urban areas, respectively. Density functional theory calculations further explained its possible degradation mechanism in atmosphere. Our work provides basic evidence for future molecular design of environmental-friendly CC containing substances. Highlights: Great environmental potential of CF3 CCH as novel refrigerant was suggested. Atmospheric lifetime is ∼53.9 d, and POCP is 1.05–2.49. 100-year GWP is 11. CO, CO2, COF2 and CF3 O3 CF3 are main carbon-containing products. Complete degradation mechanism of CF3 CCH in atmosphere was proposed. CC redistributes electrons in molecules, slightly reducing OH-initiated reactivity.